The Effect Of Delegation Of Duties And Integration On Performance Of Employees In The Office Of The Dprd Of Serdang Bedagai Regency - Hardi Mulyono (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether the delegation of tasks and integration have a significant influence on the performance of employees at the DPRD Office of Serdang Bedagai Regency. The method used in this study is a quantitative method with several tests, namely reliability analysis, classical assumption deviation test and linear regression. Based on the results of the primary data regression which was processed using SPSS 18, the following multiple linear regression equation was obtained: Y =1,288+0.313+0.664+ e. Partially, the task delegation variable (X1) has a positive and significant effect on employee performance, as evidenced by the t count > t table (5.595 > 1.991). The integration variable (X2) has a positive and significant effect on employee performance, as evidenced by the value of t count > t table (11,262 > 1,991). Simultaneously, the variables of task delegation (X1) and integration (X2) have a positive and significant effect on employee performance. This means that the hypothesis in this study is accepted, as evidenced by the calculated F value > F table (241,700 > 3.12). The variable of task delegation (X1) and integration (X2) is able to contribute influence on the service quality variable by 86.3% while the remaining 13.7% is influenced by other variables not examined in this study.should be the leaderThe Office of the Regional Representative Council of Serdang Bedagai Regency can provide objective delegation of tasks so that all employees get the appropriate work tupoksi. Employees should be able to work with high dedication so that the office can consider employee career paths.